اسهامات قانون الرياضة في ترقية التربية الصحية من خلال الرياضة المدرسية - بوساق, فتيحة; ملياني, صليحة; بوساق, اسماء (My University, 2022)
تساهم المشاركة الإيجابية من الأفراد في تحقيق أهداف الصحة العامة، وهذا ما يضع بعض المسؤوليات والمهام تقع على عاتق العاملين فى مجال الصحة بسعيهم لحث الافراد للقيام بمسؤولياتهم تجاه صحتهم، ويتم ذلك عن طريق نشر الوعي الصحي بمختلف الوسائل المتاحة، وللدولة الأثر المباشر في نشره من خلال وضعها لآليات مختلفة منها الآليات القانونية ممثلة في اصدارها لتشريعات تنظيمية، بالاضافة الى توفيرها للهياكل القاعدية كالمنشآت الرياضية والملاعب وقاعات التدريب خدمة للرياضة بأنواعها الفردية والجماعية، من اجل دعم وتشجيع الرياضة المدرسية إيمانا منها أن تكوين النشئ يساهم في خلق جيل كامل يتمتع بصحة جيدة ويملك ثقافة التربية الصحية، وبالتالي غرس فكرة " الانتقال من ثقافة الجهد إلى فائدة الجسد ". Positive participation from individuals contributes to achieving public health goals, and that’s what sets some responsibilities and tasks on the shoulders of health workers in their quest to urge individuals to fulfill their responsibilities towards their health, and this is done by spreading health awareness by various available means, and the state has a direct impact on spreading it Through setting up various mechanisms, including the legal mechanisms represented in issuing regulatory legislation, in addition to providing basic structures such as sports facilities, stadiums and training halls in the service of individual and collective sports, in order to support and encourage school sports, believing that the formation of young people contributes to the creation of a whole generation that enjoys good health and owns The culture of health education, and thus the inculcation of the idea of "moving from the culture of effort to the benefit of the body
The Contribution of sports Acts in promoting health education through school sports
مقال
Keywords: اسهامات، التربية الصحية، القانون، الرياضة المدرسية، المدارس; The Contributions, Health Education, Acts, School Sports, Schools.